Remittance and Economic Growth of Nepal - Gautam, Subas (Academia Research Journal, 2026)
Nepal heavily depends on remittance inflows that have greatly increased the GDP, alleviated poverty, and positively affected the standards of living, although they encourage unchecked imports and spending, thus discouraging the future increase in growth and productive investments. Remittances by expatriate workers especially in the Middle East and Malaysia are vital to the country and Nepal is currently one of the leading remittances receiving countries in the world although policies are required to push more productive exploitation of the funds. In this paper, the findings will be reviewed on the effects of remittance inflow on the Nepal economy between the years of 2014/15 and 2021/22 based on time series analysis and economic methods. The findings indicate that the remittance inflow produces a positive and significant impact on the economic growth of the country, and on the private consumption and investment and government revenues. The research also established that remittance inflow-economic growth interaction is more nonlinear and inverted U-shaped, which means that remittance inflow may positively influence the growth of an economy to a specific point, after which it might adversely affect this situation. In addition, the research finds that there are challenges relating to the inflow of remittance which include the fact that remittance inflow depends on the state of the global economy, remittance inflow contributes to income inequality and the fact that there is a need to have effective policies to use the remittance inflow to make productive investments.